1994
DOI: 10.2307/2410389
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, Acclimatization, and Ontogenetic Effects on Habitat Selection Behavior in Daphnia pulicaria

Abstract: Daphnia pulicaria from three different populations were observed to express within-population variation in habitat-choice behavior in field assays. Individuals from different habitats (i.e., lake depths) were isolated and cultured as clonal lines under standard conditions. Habitat choices by clonal descendants were then estimated in the field, using replicate experimental columns. There was significant heritable and ontogenetic variation in habitat choice, but the heritable effect was small relative to the phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 17 publications
2
24
0
Order By: Relevance
“…preferences for habitats and social environments will, if those dispersers have a choice of areas in which to settle, lead to systematic variation among dispersers in the conditions they experience for a period of time after that dispersal event. Several authors have reported broad-sense heritable variation in preferences for habitat features (Leibold et al 1994;Barker & Starmer 1999), and social group sizes (Brown & Brown 2000;Serrano & Tella 2007), supporting the notion that animals with different genotypes and any PEFs associated with those genotypes may, at a given age or life stage, prefer different types of environments, potentially leading to rGE (Plomin et al 1977). Similarly, individuals may, by their own behaviour, modify the social or physical environment in which they develop (niche-construction).…”
Section: Genes Experience and Contextual Generalitymentioning
confidence: 86%
“…preferences for habitats and social environments will, if those dispersers have a choice of areas in which to settle, lead to systematic variation among dispersers in the conditions they experience for a period of time after that dispersal event. Several authors have reported broad-sense heritable variation in preferences for habitat features (Leibold et al 1994;Barker & Starmer 1999), and social group sizes (Brown & Brown 2000;Serrano & Tella 2007), supporting the notion that animals with different genotypes and any PEFs associated with those genotypes may, at a given age or life stage, prefer different types of environments, potentially leading to rGE (Plomin et al 1977). Similarly, individuals may, by their own behaviour, modify the social or physical environment in which they develop (niche-construction).…”
Section: Genes Experience and Contextual Generalitymentioning
confidence: 86%
“…We recorded the number of juvenile and adult D. pulicaria separately based on a size cutoff of 1.5 mm total body length (chosen as the smallest size at which D. pulicaria commonly begins to lay eggs in these populations). Previous work has shown that habitat use behavior by this species varies between juveniles and adults of the same clones (Leibold et al 1994): juveniles chose shallower habitats than adults. Because our interest is to relate habitat use to genetic variation in adult traits, in this paper we present only the results of adult habitat use.…”
Section: Lake Samplingmentioning
confidence: 87%
“…For the past decade, plankton ecologists have worked intensively on zooplankton diel migration, habitat selection, and response to changes in planktivory, and resource availability, (e.g. , Ohman 1990;Leibold 1991;Dini and Carpenter 1992;Leibold and Tessier 1996), but have only very recently considered the genetic component of these traits (see DeMeester 1993DeMeester , 1995Mü ller and Seitz 1993;Leibold et al 1994;King and Miracle 1995;Geedey et al 1996). While there is now ample evidence of genetic variation within Daphnia populations for important ecological traits, (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Migration patterns of different development and/or reproductive stages of Bythotrephes varied according to the predictions of current DVM theory. Larger zooplankton have been repeatedly observed to reside at greater day depths than smaller individuals (, Leibold et al 1994). The brood sac of Bythotrephes with embryos is almost as large as the body of Bythotrephes itself, and the colored eyes of embryos enhance the conspicuousness of Bythotrephes females further, as was demonstrated also for gravid females of daphnids (Koufopanou and Bell 1984), copepods (Winfield and Townsend 1983), and prawns (Berglund and Rosenquist 1986).…”
Section: Discussionmentioning
confidence: 99%